A economia circular e as barreiras para a sua implementação - Rebuci, Lorena Ariesley (2022)
This dissertation has Circular Economy as its central theme. Specifically, it seeks to answer the following research question: which barriers, according to the scientific literature of the Scopus database, exist for implementing the Circular Economy in the world scenario? The objective was to identify and categorize the barriers based on state of the art on the subject. As a methodological path, the own tools of Base Scopus were used to search and select the analyzed bibliography. The analysis is proposed by Bardin (2006) methodologically oriented content analysis. In response to the question raised, the following barriers were identified and categorized: cultural barriers; financial/economic barriers; technological barriers; legislative/regulatory barriers; supply chain barriers. The conclusions reached are among the main barriers selected. The most common in the articles studied are cultural barriers, financial/economic barriers, and legislative/regulatory barriers. It is concluded, however, that these barriers are interlinked and conditioned by the economic context of each country. Finally, it is evident that the circular economy still requires optimization in the global scenario to become efficient.